Welding-free tent upright post capable of being fixed with ground - LING XINRAN; DI CHANGJUN (2016)
The invention discloses a welding-free tent upright post capable of being fixed with the ground. The welding-free tent upright post comprises an upper post, a lower post and a base, wherein the upper post comprises a top post, a bushing and an upper rod; the top post is inserted and connected into the upper rod through the bushing; the upper end of the bushing is provided with an upper end step used for limiting the position of the upper rod; the lower end of the bushing is provided with a lower end step used for limiting the position of the top post; the lower post comprises a sleeve, a lower rod and an elastic sheet; the sleeve sleeves the lower rod; the elastic sheet is arranged in the lower rod; the lower post is connected with the base through the elastic sheet; a sharp end ground nail inserted into the ground is arranged at the lower end of the base. The welding-free tent upright post has the advantages that the structure is simple; the assembly is convenient; the manufacturing cost is low. 本发明公开了种免焊接并可